1985
DOI: 10.1021/jm00149a021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of blood platelet aggregation. Effects of some 1,2-benzisothiazol-3-ones on platelet responsiveness to adenosine diphosphate and collagen

Abstract: A series of substituted 1,2-benzisothiazol-3-ones was synthesized, and the compounds were tested for ability to inhibit platelet aggregation induced by adenosine diphosphate and collagen in rats and guinea pigs ex vivo. Alkyl substituents at the 2-position bearing a basic group were necessary for ex vivo activity. Several of the compounds were potent inhibitors of adenosine diphosphate induced first-phase aggregation, but adverse toxicological findings terminated their further development. Preliminary studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…For the synthesis of N -substituted benzisothiazol-3(2 H )-ones 2 the analogous reaction of 2-(chlorosulfanyl)benzoyl chloride ( 12 ) , obtained in a two-step synthesis starting from 2,2’-dithiodibenzoic acid ( 14 ) [ 11 ], with corresponding primary amines has been adapted. This reaction has already been successfully used with some primary amines [ 12 ], hydrazine derivatives [ 13 ] and amino acids [ 14 , 15 ] as reactants. Our further studies have demonstrated that the reactions of chloride 12 with other N -nucleophiles, e.g., thiourea, thioacetamide, acetamide and p-methylbenzenesulfonamide also resulted in N -substituted benzisothiazol-3(2 H )-ones, while reactions with CH -acids gave corresponding benzo[ b ]thiophen-3(2 H )-ones or/and 3-hydroxybenzo[ b ]thiophenes [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of N -substituted benzisothiazol-3(2 H )-ones 2 the analogous reaction of 2-(chlorosulfanyl)benzoyl chloride ( 12 ) , obtained in a two-step synthesis starting from 2,2’-dithiodibenzoic acid ( 14 ) [ 11 ], with corresponding primary amines has been adapted. This reaction has already been successfully used with some primary amines [ 12 ], hydrazine derivatives [ 13 ] and amino acids [ 14 , 15 ] as reactants. Our further studies have demonstrated that the reactions of chloride 12 with other N -nucleophiles, e.g., thiourea, thioacetamide, acetamide and p-methylbenzenesulfonamide also resulted in N -substituted benzisothiazol-3(2 H )-ones, while reactions with CH -acids gave corresponding benzo[ b ]thiophen-3(2 H )-ones or/and 3-hydroxybenzo[ b ]thiophenes [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 Among these, isothiazolones and benzisothiazolones (BIT) constitute an important class due to the presence of electrophilic sulfur as part of the ring. 2,3 The capability of these compounds to form disulde bonds with sulfur nucleophiles or to chelate biologically relevant metals such as zinc 4,5 has been correlated with their activities against human leukocyte elastase, [6][7][8][9] RNA polymerase, proteases, 10,11 HIV-NcP-7, 12 telomerase, 13,14 blood platelet aggregation, 15 microbes, [16][17][18] and proliferation. 19,20 Recently, Groutas and co-workers have evaluated the activities of benzisothiazolone derivatives against fungal strains, 21 and viruses causing Dengue and West Nile fever.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, isothiazolone derivatives have played an essential role in biology and medicine by virtue of their antibacterial, [1] antipsychotic, [2] antiviral, [3] antithrombotic, [4] and analgesic activities [5] . For instance, 1,2‐benzisothiazol‐3(2 H )‐one derivatives, [6a] substituted N ‐phenylisothiazolones, [6b] 2‐[3‐(trifluoromethyl)‐phenyl]isothiazolinone, [6c] and 2,5‐diarylisothiazolones [6d] have been reported as inhibitors of fungus, histone acetyl transferase, telomerase, and cartilage destruction, respectively (Figure 1).…”
Section: Figurementioning
confidence: 99%